Spectroscopic and Gas Chromatographic Studies of Pigments and Binders in Gdańsk Paintings of the 17th Century - Justyna Olszewska-Świetlik; Bożena Szmelter-Fausek; Ewa Pięta; Edyta Proniewicz (Journal of Spectroscopy)
This work presents spectroscopic (optical microscopy, OM; micro-Raman, Raman; and Fourier-transform adsorption infrared, FT-IR) and gas chromatographic studies of two famous panel paintings from the Gdańsk artists of the 17th century Golden Age, “Servilius Appius” by Isaac van den Blocke and “Allegory of Wealth” probably by Anton Möller. Application of the aforementioned methods allowed us to identify pigments and binders used in the panel paintings. In particular, it was determined that the yellow pigment used by both artists is lead-tin yellow type I (2PbO·SnO2), the white pigment is lead (II) carbonate hydroxide (2PbCO3·Pb(OH)2), and the ground layer material consist of chalk (CaCO3). The analysis showed also that in the case of “Allegory of Wealth,” the red layer consists not only of cinnabar (HgS) but also of lead-tin yellow type I.